The Fatalistic Decision Maker: Time Perspective, Working Memory, and Older Adults’ Decision-Making Competence - Rönnlund, Michael; Del Missier, Fabio; Mäntylä, Timo; Carelli, Maria Grazia (Frontiers in Psychology, 2019)
Prior research indicates that time perspective (TP; views of past, present and future) is related to decision making style. By contrast, no prior study considered relations between time perspective and decision-making competence. We therefore investigated associations between dimensions of the Swedish Zimbardo Time Perspective Inventory (S-ZTPI) and performance on the Adult Decision-Making Competence (A-DMC) battery in a sample of older adults (60-90 years, N = 346). A structural equation model involving four A-DMC components as indicators of a general DMC factor and the six TP dimensions as the predictors revealed a significant negative association between the Present Fatalistic dimension and DMC. Given that age-related differences were apparent in DMC and that Present Fatalistic orientation increased with age, we tested a model by which the age-related differences in DMC were mediated by age-related differences in Present Fatalistic attitudes and in working memory. The results were consistent with full mediation of the age effects, with Present Fatalistic and working memory jointly accounting for a substantial amount of the variance in DMC (51%). The finding that DMC among older adults, in particular more cognitively demanding aspects such as applying decision rules, can be undermined by increased present fatalistic attitudes and declines in working memory is discussed in terms of theoretical frameworks highlighting the contribution of both motivational and cognitive factors to effective decision making.